Genetic variations of Toll-like receptor 4 gene in exon 2 of South African Dorper sheep (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study was conducted to identify the sequence variation of Toll-like receptor 4 (TLR4) in exon 2 of South African Dorper sheep.Materials and Methods: Blood samples were collected from fifty (n = 50) South African Dorper sheep aged between 3 and 4 years. The Deoxyribonucleic acid (DNA) was extracted, amplified, and sequenced for the TLR4 gene. DNA sequencing was used to identify the sequence variations of the TLR4 gene in South African Dorper sheep.Results: The results showed that one synonymous single nucleotide polymorphism (SNP) of the TLR4 gene in exon 2 position T2249C was identified. Two genotypes (TT and TC) were discovered from the identified SNP. The dominant genotype was TT (0.60) over TC (0.40), with the dominant allele T (0.80) over C (0.20). The results also indicated that the used population was in the Hady-Weinberg Equilibrium. Polymorphism genetic analysis findings suggest that the identified sequence variation of TLR4 in exon 2 of South African Dorper sheep was moderate polymorphism.Conclusion: TLR4 gene at exon 2 of South African Dorper sheep had the SNP (T>C) at position 2249 bp with two genotypes (TT and TC).Adv. Vet. Anim. Res., 11(2): 302-305, June 2024http://doi.org/10.5455/javar.2024.k777